Advances of Stem Cell Therapeutics in Cutaneous Wound Healing and Regeneration - Suman Kanji; Hiranmoy Das (Hindawi Limited, 2017)
Cutaneous wound healing is a complex multiple phase process, which overlaps each other, where several growth factors, cytokines, chemokines, and various cells interact in a well-orchestrated manner. However, an imbalance in any of these phases and factors may lead to disruption in harmony of normal wound healing process, resulting in transformation towards chronic nonhealing wounds and abnormal scar formation. Although various therapeutic interventions are available to treat chronic wounds, current wound-care has met with limited success. Progenitor stem cells possess potential therapeutic ability to overcome limitations of the present treatments as it offers accelerated wound repair with tissue regeneration. A substantial number of stem cell therapies for cutaneous wounds are currently under development as a result of encouraging preliminary findings in both preclinical and clinical studies. However, the mechanisms by which these stem cells contribute to the healing process have yet to be elucidated. In this review, we emphasize on the major treatment modalities currently available for the treatment of the wound, role of various interstitial stem cells and exogenous adult stem cells in cutaneous wound healing, and possible mechanisms involved in the healing process.